Long-Term Habitat Degradation Drives Neotropical Macrophyte Species Loss While Assisting the Spread of Invasive Plant Species - Salgado, Jorge; Vélez, María I.; Caceres-Torres, Laura C.; Villegas-Ibagon, Jose A.; Bernal-Gonzalez, Laura C.; Lopera-Congote, Laura; Martinez-Medina, N. Melissa; González-Arango, Catalina (Frontiers in Ecology and Evolution, 2019)
Macrophyte invasive species spreading is one of the most pressing threats to tropical shallow lakes. Yet, studies addressing the full extent of biotic and abiotic changes that may occur in response to invasive species are poorly documented. Less known is how other human-induced stressors such as eutrophication and lake draining may interact over time with invasive macrophytes to jointly influence biodiversity loss. We combined ecological and limnological observations with paleoecological data from a eutrophic Neotropical shallow lake, Fúquene Lake, Colombia, to provide information on the current and long-term (decades-centuries) dynamics of spread of two well-established invasive plants Eichhornia crassipes and Egeria densa. At present-day, areas dominated by Egeria and Eichhornia were unique in macrophyte structure and differed from those areas having a mixture of macrophyte species or open waters. Eichhornia areas encompassed 14 macrophyte species and had turbid (secchi=19 ±6 cm) and poorly oxygenated (3.94 ±2.61 ppm) waters. Egeria areas had clearer (secchi=51 ±12 cm) and better-oxygenated (6.06 ± 2.4 ppm) waters supporting six macrophyte species. Historical macrophyte community shifts were linked to eutrophication and hydrological alteration exemplify by losses of charophytes and bryophytes before 1500 CE and subsequent reductions in Nymphaea sp., Potamogeton illinoensis and Najas guadalupensis in the early 1900s (lake draining). E. crassipes (since 1500 CE) and E. densa (early 1900s) occurred well before suggested dates of introduction (1950s and 1990 respectively). Yet, they severely expanded since the 1990s along with Azolla filiculoides in response to an inflow waters diversion scheme and heavy nutrient load. Results suggest that the spread of Eichhornia and Egeria was not responsible for historical resident species loss. Nevertheless, their current domination is exerting synergetic and antagonistic secondary effects on plant assemblages through habitat modification, competitive exclusion and promotion of habitat spatial heterogeneity across the lake. Equating macrophyte species loss with invasive plants spreading in degraded lakes could be therefore misleading. Aggressive species like Eichhornia, Azolla and Egeria are suggested to require eutrophic environments to spread, thus, management actions should focus on controlling nutrient load. Our study demonstrates the need of addressing long-term approaches to fully-understanding the effects of invasive macrophyte spread.